2013
DOI: 10.1021/jp402141f
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Flow Enhancement Factor and Structure for Core-Softened Fluids Inside Nanotubes

Abstract: The relationship between enhancement flow and structure of core-softened fluids confined inside nanotubes has been studied using nonequilibrium molecular dynamics simulation. The fluid was modeled with different types of attractive and purely repulsive two length scale potentials. Such potentials reproduce in bulk the anomalous behavior observed for liquid water. The dual control volume grand canonical molecular dynamics method was employed to create a pressure gradient between two reservoirs connected by a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
70
0
4

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(85 citation statements)
references
References 66 publications
11
70
0
4
Order By: Relevance
“…[43][44][45][46] CS fluids confined in nanotubes also present interesting findings, similar to obtained in atomistic models for water, as the increase in diffusion coefficient and flux for narrow nanotubes associated to a layer to single-file transition and a discontinuity in the enhancement flow factor. [47][48][49] The drawback of these core-softened potentials is that due to the simplicity of the two length scales, they are not capable to reproduce the effects related to the third coordination shell of the anomalous fluid what might be relevant under confinement. 50 In addition to the relevance of the detail structure of the liquid, the structure of the confining system is also relevant since biological and physical materials do not exhibit the smoothness and regularity of the flat walls and tubes employed in the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46] CS fluids confined in nanotubes also present interesting findings, similar to obtained in atomistic models for water, as the increase in diffusion coefficient and flux for narrow nanotubes associated to a layer to single-file transition and a discontinuity in the enhancement flow factor. [47][48][49] The drawback of these core-softened potentials is that due to the simplicity of the two length scales, they are not capable to reproduce the effects related to the third coordination shell of the anomalous fluid what might be relevant under confinement. 50 In addition to the relevance of the detail structure of the liquid, the structure of the confining system is also relevant since biological and physical materials do not exhibit the smoothness and regularity of the flat walls and tubes employed in the simulations.…”
Section: Introductionmentioning
confidence: 99%
“…In order to answer these questions water-like atomistic or continuous effective potential models were explored. The confining geometries could be plates [27][28][29][30][31][32][33][34][35][36][37], one pore [38][39][40][41][42][43][44][45][46], and a disordered matrix [43,52,53,[55][56][57]. The results for the melting temperature obtained within these approaches are controversial, while results for SPC/E water show that the melting temperature for hydrophobic plates is lower than the melting for the unconfined system and higher than for the system confined by hydrophilic walls, for the mW model no difference between the melting temperatures due to the hydrophobicity [47] is found.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 Recently, it has been suggested that core-softened potential models are able to capture some of the anomalous behavior even under confinement. [43][44][45][46][47] In fact, the behavior of the diffusion constant for nanoconfined water, attributed to the hydrogen bonds, 48 was obtained by pure volumetric effects in these isotropic anomalous fluids. 46 Motivated by this proposition, in this paper we use NEMD simulation in order to explore the connection between the enhanced particle flow and the fluid-fluid interaction potential for fluids confined inside a nanopore.…”
Section: Introductionmentioning
confidence: 99%
“…46 Motivated by this proposition, in this paper we use NEMD simulation in order to explore the connection between the enhanced particle flow and the fluid-fluid interaction potential for fluids confined inside a nanopore. In order to avoid misleadings, we should address that in the literature, 25,27,47 it is usual to evaluate the flow enhancement factor, which can be defined as the ratio between the hydraulic conductivity obtained using molecular simulations and the hydraulic conductivity predicted by classical continuum models. In our paper, the enhanced flow is the anomalous increase of particle flow in narrow nanotubes, and will not be compared with the results of classical continuum theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation